2016
DOI: 10.1038/modpathol.2016.113
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-cell lymphomas of follicular helper T-cell type frequently display an aberrant CD3−/dimCD4+ population by flow cytometry: an important clue to the diagnosis of a Hodgkin lymphoma mimic

Abstract: Nodal follicular helper T-cell-derived lymphoproliferations (specifically the less common peripheral T-cell lymphomas of follicular type) exhibit a spectrum of histologic features that may mimic reactive hyperplasia or Hodgkin lymphoma. Even though angioimmunoblastic T-cell lymphoma and peripheral T-cell lymphoma of follicular type share a common biologic origin from follicular helper T-cells and their morphology has been well characterized, flow cytometry of peripheral T-cell lymphomas of follicular type has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 35 publications
3
25
1
Order By: Relevance
“…In tissue samples, we frequently encountered that other standard TFH markers were not informative by immunohistochemistry, or interpretation of immunohistochemistry was challenging. In our cohort, expression of other TFH markers was not observed by immunohistochemistry in seven cases (25% of cases; Case #3, 7,8,12,15,19,28). Additional three cases (11% of cases; Case #21, 22, 27) presented with concomitant lymphoid neoplasm, which obscured morphologic and immunohistochemical evaluation for AITL ( Fig.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…In tissue samples, we frequently encountered that other standard TFH markers were not informative by immunohistochemistry, or interpretation of immunohistochemistry was challenging. In our cohort, expression of other TFH markers was not observed by immunohistochemistry in seven cases (25% of cases; Case #3, 7,8,12,15,19,28). Additional three cases (11% of cases; Case #21, 22, 27) presented with concomitant lymphoid neoplasm, which obscured morphologic and immunohistochemical evaluation for AITL ( Fig.…”
mentioning
confidence: 57%
“…Previous studies identified abnormal T-cell population with sCD3-/CD4+immunophenotype in AITL [9][10][11][12][13] . In our cohort,~15% of AITL show two distinct abnormal T-cell populations with and without surface CD3 expression (Case 10, 12, 17, 23).…”
mentioning
confidence: 93%
“…4). 24,48,52,53 A chromosomal translocation t(5;9)(q33;q22) involving ITK and SYK tyrosine kinases is found in about 20% of F-PTCL, and has been reported thus far in only one case of typical AITL. 48,54,55 The ITK-SYK fusion may be detected by fluorescence in situ hybridisation (FISH) assays, but its diagnostic value is rather limited.…”
Section: Follicular T-cell Lymphoma (F-ptcl)mentioning
confidence: 99%
“…With Hodgkin’s lymphoma in particular, Gaulard et al first noted the utility of combining histology and immunohistochemistry to reveal a clonal T-cell population to distinguish the aforementioned entities 26. Further research has shown that the presence of an aberrant CD3(-dim) CD4(+) population by flow cytometry is displayed in PTCL of follicular helper type 27. Using said flow cytometry and clonal PCR can even help distinguish the rare entity of a Hodgkin’s lymphoma with expressing a T-cell antigen 28 29.…”
Section: Discussionmentioning
confidence: 99%